1.01(1.27)(9-x)=11

Simple and best practice solution for 1.01(1.27)(9-x)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.01(1.27)(9-x)=11 equation:


Simplifying
1.01(1.27)(9 + -1x) = 11

Multiply 1.01 * 1.27
1.2827(9 + -1x) = 11
(9 * 1.2827 + -1x * 1.2827) = 11
(11.5443 + -1.2827x) = 11

Solving
11.5443 + -1.2827x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11.5443' to each side of the equation.
11.5443 + -11.5443 + -1.2827x = 11 + -11.5443

Combine like terms: 11.5443 + -11.5443 = 0.0000
0.0000 + -1.2827x = 11 + -11.5443
-1.2827x = 11 + -11.5443

Combine like terms: 11 + -11.5443 = -0.5443
-1.2827x = -0.5443

Divide each side by '-1.2827'.
x = 0.4243392843

Simplifying
x = 0.4243392843

See similar equations:

| 4b=2b-1 | | 5.5y-6.1=19.20 | | b=3/4 | | 24(1.5+3)=n | | 8z(squared)=6z(squared)+38 | | x+27.3=8.9 | | m/-10=12=67 | | (7/10)/(5/16) | | 4x-5+2x+15=130 | | 4(3-5p)=9p-278 | | 2b+3=46-4 | | v^2+7=32 | | 4/9=x/11 | | 1.5+3=24 | | x-19=8x+2 | | -4y-15=-2y+5 | | 38(17-5.5x)=13(5x-9)+23.2 | | 24=1.5+3 | | 168*0.8=134 | | 110=6b+4b | | (x-5)-3=-28 | | 3(9y-2.6)+7.2=6(8y-0.1) | | -5b^2=-180 | | 3y-2x=.5 | | m=-1/4,b=3/5 | | 3c+2c=-95 | | -1.56-2.6y=2.6(y+8.8) | | 18=3s-10+4s | | 9y-8=7y+8 | | 7(x+2.1)=14x-2.8 | | -5x+16=-8(x+1)+6x | | 11=3c+5 |

Equations solver categories